2022
DOI: 10.1515/ract-2021-1120
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical insights into the reduction mechanism of neptunyl nitrate by hydrazine derivatives

Abstract: In the advanced spent fuel cycle, the control and adjustment of neptunium valence state is greatly important for the highly efficient separation of neptunium. Hydrazine and its derivatives as salt-free reagents can selectively reduce Np(VI) to Np(V), but their reduction mechanisms are still unclear. We explored the reduction of [NpVIO2(H2O)2(NO3)2] by N2H4 and its two derivatives HOC2H4N2H3 and CHON2H3 using scalar relativistic density functional theory. The thermodynamic energy of the reactions [NpVIO2(H2O)2(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…We have theoretically examined the reaction mechanisms of Np­(VI) by hydrazine, and its derivates, and found that their reduction ability based on the theoretical energy barrier is consistent with the experimental results. , These results also confirm that the B3LYP/ECP60MWB/6-31G­(d) level of theory used in our previous studies is suitable for the systems of Np­(VI) reduction. In this work, we have further clarified the reduction mechanism of Np­(VI) by carbohydrazide at the B3LYP/ECP60MWB/6-31G­(d) level of theory.…”
Section: Introductionsupporting
confidence: 73%
“…We have theoretically examined the reaction mechanisms of Np­(VI) by hydrazine, and its derivates, and found that their reduction ability based on the theoretical energy barrier is consistent with the experimental results. , These results also confirm that the B3LYP/ECP60MWB/6-31G­(d) level of theory used in our previous studies is suitable for the systems of Np­(VI) reduction. In this work, we have further clarified the reduction mechanism of Np­(VI) by carbohydrazide at the B3LYP/ECP60MWB/6-31G­(d) level of theory.…”
Section: Introductionsupporting
confidence: 73%